Antibiogram and β-Lactamase Test of Multidrug Resistant Staphylococcus Species - Shrestha, C; Rajbahak, S; Shrestha, J; Singh, A (Scientific World, 2013)
No Abstract Available Scientific World, Vol. 11, No. 11, July 2013, page 70-73